Nanostructured CuS networks composed of interconnected nanoparticles for asymmetric supercapacitors. Issue 35 (19th August 2016) - Fu, Wenbin; Han, Weihua; Zha, Heming; Mei, Junfeng; Li, Yunxia; Zhang, Zemin; Xie, Erqing
Abstract : Nanostructured CuS networks composed of interconnected nanoparticles are demonstrated as promising electrodes for asymmetric supercapacitors. Abstract : Nanostructured metal sulfides with excellent electrochemical activity and electrical conductivity are particularly promising for applications in high-performance energy storage devices. Here, we report on the facile synthesis of nanostructured CuS networks composed of interconnected nanoparticles as novel battery-type materials for asymmetric supercapacitors. We find that the CuS networks exhibit a high specific capacity of 49.8 mA g −1 at a current density of 1 A g −1, good rate capability and cycle stability. The superior performance could be attributed to the interconnected nanoparticles of CuS networks, which can facilitate electrolyte diffusion and provide fast electron pathways. Furthermore, an aqueous asymmetric supercapacitor has been assembled by using the CuS networks as the positive electrode and activated carbon as the negative electrode. The assembled device can work at a high operating voltage of 1.6 V and show a maximum energy density of 17.7 W h kg −1 at a power density of 504 W kg −1 . This study indicates that the CuS networks have great potential for supercapacitor applications.